2013
DOI: 10.1016/j.lfs.2012.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic activation of TRP receptors by endogenous lipids: Exploiting lipidomics to understand TRP receptor cellular communication

Abstract: Transient receptor potential channels (TRPs) form a large family of ubiquitous non-selective cation channels that function as cellular sensors and in many cases regulate intracellular calcium. Identification of the endogenous ligands that activate these TRP receptors is still under intense investigation with the majority of these channels still remaining “orphans”. That these channels respond to a variety of external stimuli (e.g. plant-derived lipids, changes in temperature, and changes in pH) provides a fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 59 publications
(68 reference statements)
2
34
0
Order By: Relevance
“…Fatty acid acylamides are a group of lipid derivatives related to endogenous cannabinoid mediators. Some fatty acid acylamides were shown to activate TRP ion channels, including TRPV1 and TRPV4 (6,29). Although the injury-induced concentrations of individual injury-induced fatty acid acylamides in BALF or lung tissue samples were low, we found Untreated TRPV6 TRPV5 TRPV4 TRPV3 TRPV2 TRPV1 TRPM8 TRPM7 TRPM6 TRPM5 TRPM4 TRPM3 TRPM2 TRPM1 TRPC7 TRPC6 TRPC5 TRPC4 TRPC3 TRPC2 TRPC1 TRPA1 FPKM 0 almost all tested species (Ͼ10) to be increased.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Fatty acid acylamides are a group of lipid derivatives related to endogenous cannabinoid mediators. Some fatty acid acylamides were shown to activate TRP ion channels, including TRPV1 and TRPV4 (6,29). Although the injury-induced concentrations of individual injury-induced fatty acid acylamides in BALF or lung tissue samples were low, we found Untreated TRPV6 TRPV5 TRPV4 TRPV3 TRPV2 TRPV1 TRPM8 TRPM7 TRPM6 TRPM5 TRPM4 TRPM3 TRPM2 TRPM1 TRPC7 TRPC6 TRPC5 TRPC4 TRPC3 TRPC2 TRPC1 TRPA1 FPKM 0 almost all tested species (Ͼ10) to be increased.…”
Section: Discussionmentioning
confidence: 61%
“…In our present study we focused on N-acyl amines, fatty acidderived products related to anandamide and similar endocannabinoids (6). N-acyl amides are known to activate TRP ion channels, including TRPV4 (6,29). Exposure to chlorine, or intratracheal administration of HCl, resulted in increases of almost all N-acyl amides we tested for in both BALF and total lung tissue, suggesting that multiple TRP channel agonists are produced following ALI (Table 3).…”
Section: Diminished Acid-induced Pulmonary Inflammation In Mice Treatmentioning
confidence: 96%
See 1 more Smart Citation
“…Much work has shown that TRPs respond to a variety of external stimuli (e.g., plant-derived lipids), however, most TRP receptors are expressed in areas that would not come in direct contact with external stimuli (e.g., CNS tissue, internal organs, smooth muscle); therefore, the mechanism of direct activation by cellular messengers is still under much debate and research. In the few cases where endogenous ligands have been identified that drive direct activation of TRPs, the majority of these ligands are small lipid molecules, most of which share structural homology (Bradshaw et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…TRPV1 ion channels have important functions as cellular sensors, and are involved in nociception, taste perception, thermosensation, mechano‐ and osmolarity sensing, and regulation of signal transmission 15, 55, 56. In addition to ECS and physicochemical activators,15, 33, 55, 56, 57, 58 TRPV1 is activated by tetrahydrocannabinol, cannabinol, cannabigerol and some propyl homologs of THC and cannabigerol 59, 60, 61, 62, 63, 64, 65, 66, 67. Cannabichromene (CBC), cannabidiol, and cannabinol are strong TRPA1 agonists and desensitizers, and THCV (from a botanical extract) is a potent regulator of TRPA1 62…”
Section: The Endocannabinoid Systemmentioning
confidence: 99%